IMPROVING PERFORMANCE BY ENHANCING WORK MOTIVATION AND MANAGING THE WORKLOAD OF NURSES AT CIREMAI HOSPITAL CIREBON (International Journal of Innovative Technologies in Economy, 2025)
This research seeks to investigate how job motivation and the amount of work impact the performance of nurses at Type III Hospital 03.06.01 Ciremai in Cirebon City. The study employed a quantitative research methodology using an associative approach, involving 90 nurses as respondents. The information was gathered by utilizing questionnaire and examined through several linear regressions with the support of SPSS 25. The findings indicated that both work motivation and workload have a favorable and notable impact on nurse performance. Work motivation showed a stronger influence (β = 0.376; p < 0.05) compared to workload (β = 0.189; p < 0.05). Work motivation has a stronger impact compared to the workload factor. This finding indicates that increasing work motivation and managing workload well can improve nurses' performance. Therefore, hospitals are advised to improve factors that influence work motivation, such as recognition, policies, and working conditions, and manage workload through task rotation and psychological support to ensure optimal quality of health services.